ANALISIS FAKTOR DOMINAN YANG MEMPENGARUHI KEPATUHAN PASIEN DM TIPE 2 DALAM MELAKUKAN PERAWATAN KAKI - Lina Ema Purwanti; Tetik Nurhayati (Jurnal Ilmiah Kesehatan, 2017)
Diabetes is one of the largest global health emergencies of the 21 century. Each year more and more people live with this condition, which can result in life-changing complications. (IDF Atlas, 2015). Diabetes Mellitus (DM) if uncontrolled can cause acute and chronic complications that result in disability and even death. Compliance in foot care has an important role in the therapeutic management of patients with DM. The purpose of this study was to identify dominan factors affecting the compliance of patients Type 2 DM to foot care. Method: The research design was correlations with cross sectional approach, conducted on 77 patients with Type 2 DM that managed by Prolanis in Ponorogo. Result: The results showed that perception of seriousness (p value 0.014), and the perception of benefits (p value 0.025) significantly influence the compliance of patients with Type 2 DM to foot care (α = 0.05). Conclusions: Knowing the dominant factors that influence patient compliance with Type 2 Diabetes Mellitus in doing foot care can become a non-pharmacological preventive measures to prevent the risk of developing diabetic foot amputation due to disability and death in DM client.